Analysis and reflection of the current situation in the field of occupational health and safety management in Сhina construction enterprises - Liu, Yujun; Євтушенко, Наталія Сергіївна (Харківський національний університет міського господарства ім. О. М. Бекетова, 2023)
With the continuous development and progress of China's economy, people pay more and more attention to safety in the production operation. China has issued a series of laws, regulations, regulations and safety technical standards in road and bridge construction safety production management, and has established a relatively complete organization system of road and bridge construction safety management, and road and bridge construction safety management has also made remarkable achievements. However, the accident frequency is still at a high level in road and bridge construction.
Keywords: labor protection; labor protection audit; working conditions; occupational safetyі